Faktor-Faktor yang Mempengaruhi Lama Rawat Inap pada Pasien Demam Berdarah Dengue di Rumah Sakit Umum Cut Meutia - Risky Ananda Putra; Rizka Sofia; Wizar Putri Mellaratna (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2026)
Dengue Hemorrhagic Fever (DHF) is an infection caused by the dengue virus transmitted by the Aedes aegypti mosquito, which has become a leading cause of death and requires hospitalization in most cases. Managing DHF patients requires a long time and relatively large costs. The high number of hospitalizations imposes a considerable burden. This study aims to determine the factors influencing the length of hospital stay for dengue fever patients at the Cut Meutia Regional Hospital in North Aceh Regency. This study is a descriptive analytical study with a cross-sectional approach using medical record data from January to December 2022.